Survey of noninvasive respiratory support practices in Canadian neonatal intensive care units. (25th November 2016) - Mukerji, Amit; Shah, Prakesh S.; Shivananda, Sandesh; Yee, Wendy; Read, Brooke; Minski, John; Alvaro, Ruben; Fusch, Christoph; ,
Abstract: Aim: To evaluate practice variation with respect to noninvasive respiratory support (NRS) use across Canadian neonatal intensive care units (NICUs). Methods: A web‐based survey was sent to all site investigators of the 30 level 3 NICUs participating in the Canadian Neonatal Network. The survey inquired about the use of five commonly described NRS modes. In addition, the presence and adherence to local guidelines were ascertained. Descriptive analyses were performed to identify variations in practice. Results: In total, 28 (93%) of the 30 tertiary NICUs responded to the survey. Continuous positive airway pressure (CPAP) was employed universally (100%). High‐flow nasal cannula (HFNC) was used in 89% of NICUs, biphasic CPAP in 79% and nasal intermittent positive pressure ventilation (NIPPV) in 54%, and nasal high‐frequency ventilation was used in 18% of units. Only 61% of all NRS use was guided by local policies, with the lowest being for HFNC (36%). There was a wide range of settings employed and interfaces used for all NRS modes. Conclusion: There are significant practice variations in NRS use across Canadian NICUs. Further research is needed to evaluate the significance in relation to pulmonary outcomes to determine optimal NRS strategies.